Navigating Health Care in Crises: Health Literacy and Treatment Adherence Among Hemodialysis Patients in Lebanon - Boueri, Myriam (2025)
Rationale & Objective Chronic kidney disease is projected to become the fifth most prevalent chronic condition globally by 2040, with a current prevalence of 10%-15%. This study aimed to assess treatment adherence in relation to health literacy (HL) and digital healthy diet literacy (DDL) levels of patients receiving hemodialysis in Lebanon. Study Design A multicenter, cross-sectional study was conducted during 2021-2023. Setting & Participants It included patients in 18 dialysis centers based on nonprobability sampling. Patients were eligible if they were aged 18+ years and Arabic speakers. Severe illness, dementia, and confusion were exclusion criteria. Exposure(s) Sociodemographic factors (marital status, education, governorate, employment, financial means, and fear of coronavirus disease 2019 [COVID-19]) were assessed as predictors of adherence and HL. Outcomes The primary outcomes were HL scores (Health Literacy Scale- Short Form 12), DDL scores (Digital Healthy Diet Literacy Scale), and adherence to treatment scores (treatment adherence questionnaire). Analytical Approach Bivariate analysis identified associations between patient characteristics and scores on scales. Simple linear regression was used to evaluate the relationship between scores and independent variables. Results Participants (N = 699, 64.5% male patients) showed below-average HL levels (18.96 ± 11.79) and DDL (15.95 ± 14.58), and moderate adherence behavior (995.82 ± 178.99). Single patients and those with higher educational and employment statuses had higher levels of HL. Regional disparities were observed. Individuals who did not experience financial difficulty in covering their treatment cost, and those who had less fear from COVID-19, showed higher DDL scores. Single individuals displayed lower treatment adherence. Limitations This study is limited by its cross-sectional design, and by contextual factors that affected patient attendance and researcher access to hemodialysis centers, along with overrepresentation of private facilities. Conclusions There is a need for educational programs and targeted interventions to enhance health literacy and adherence in this patient population, especially among those with lower education, financial instability, and higher fear of COVID-19.